Study protocol for a pragmatic randomised controlled trial evaluating efficacy of a smoking cessation e-'Tabac Info Service': ee-TIS trial. Issue 2 (24th February 2017) - Cambon, L; Bergman, P; Le Faou, Al; Vincent, I; Le Maitre, B; Pasquereau, A; Arwidson, P; Thomas, D; Alla, F
Abstract : Introduction: A French national smoking cessation service, Tabac Info Service, has been developed to provide an adapted quitline and a web and mobile application involving personalised contacts (eg, questionnaires, advice, activities, messages) to support smoking cessation. This paper presents the study protocol of the evaluation of the application (e-intervention Tabac Info Service (e-TIS)). The primary objective is to assess the efficacy of e-TIS. The secondary objectives are to (1) describe efficacy variations with regard to users' characteristics, (2) analyse mechanisms and contextual conditions of e-TIS efficacy. Methods and analyses: The study design is a two-arm pragmatic randomised controlled trial including a process evaluation with at least 3000 participants randomised to the intervention or to the control arm (current practices). Inclusion criteria are: aged 18 years or over, current smoker, having completed the online consent forms, possessing a mobile phone with android or apple systems and using mobile applications, wanting to stop smoking sooner or later. The primary outcome is the point prevalence abstinence of 7 days at 6 months later. Data will be analysed in intention to treat (primary) and per protocol analyses. A logistic regression will be carried out to estimate an OR (95% CI) for efficacy. A multivariate multilevel analysis will explore the influence on results of patients' characteristics (sex, age, education and socioprofessional levels, dependency, motivation, quit experiences) and contextual factors, conditions of use, behaviour change techniques. Ethics and dissemination: The study protocol was reviewed by the ethical and deontological institutional review board of the French Institute for Public Health Surveillance on 18 April 2016. The findings of this study will allow us to characterise the efficacy of e-TIS and conditions of its efficacy. These findings will be disseminated through peer-reviewed articles. Trial registration number: NCT02841683; Pre-results.